Estudio presupuestario aplicado a la construcción de la Casa Comunal en el Gobierno Autónomo Descentralizado de Píntag - Antamba Rivas, Kléber Santiago (2017)
The main purpose of this project is to provide a guide for the preparation of a constructive budget as a reference and support for rural parishes and the builder in general. In the development of the work, the main concepts related to budgetary activity divided into direct and indirect costs and all its components are exposed through a detailed study supported by information from different means, both public and private sector. This way, the elements that will allow to have the items to be used and the work quantities of each one of these that will intervene in the budgetary study for the construction of a communal house by means of different constructive methods, as well as graphs to have a better understanding and elaboration. As a result, the analysis of unit prices of each item will be obtained in order to be able to make the final budget and the estimated work schedule that will determine the time used and the value to be used. Finally, it will be possible to observe the advantages and disadvantages in carrying out this type of study and the recommendations will be obtained when making a budget taking into account all the studies proposed in this project